Aspek-Aspek Psikologis pada Prosesi Rambu Solo’ (Tinjauan Teori Religiusitas) - Reyvences Asgrenil Lusi; Listyo Yuwanto (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2020)
This literature review aims to review the psychological aspects, especially the religiosity aspects contained in the implementation of the Rambu Solo’ procession in the Toraja tribes. Rambu Solo’ is the procession of delivering or burying the dead by their families to the spiritual realm or puya (heaven). In its implementation, there are adjustments as well as shifts in the implementation of the Rambu Solo’ procession "which was carried out in the past compared to the implementation of the Rambu Solo’ today. Rambu Solo' is a concept of religiosity that exists today, especially in the Toraja tribes because this procession is carried out not only based on ancestral beliefs but also based on religious values that have entered and developed in the Toraja region.